Selangkah Lebih Maju Untuk Brand Awareness UMKM Pabissa Shoes - Michelle Clarissa Pradana; Felysia Manggala; Derryl Tungadi; Revina A. Wilar; Fernando L. C; Marchel Rocky Holiwono; Carolina Novi Mustikarini (LPPM Stikosa - AWS, 2024)
This paper is a community service journal conducted to fulfill final exam on UNC1008 EntrepreneurialVenture Innovation. This service program focused on developing UMKM Pabissa Shoes’ brandawareness. Starting from the income decrease, problem was founded, that UMKM Pabissa Shoes shouldintroduce brand awareness to larger society. To overcome this problem, using artificial intelligence tomake often creative content calendar idea, poster innovation, neon box design. Creative content calendaris beneficial for a constant uploading schedule. Moreover, poster innovation will be distributed in publicplaces. Then, neon box design is to renew the outside looks of the shop. To conclude, brand awarenessis the main key of business.